Giving green grass jelly for mda (malondialdehyde) level in pregnant women with hypertension - Meika Jaya Rochkmana; Ari Suwondo; Sulistyani Sulistyani (Alma Ata University Press, 2022)
Background: Hypertension is a disease that often occurs during pregnancy. Many factors influence the occurrence of hypertension, one of which is oxidative stress. Oxidative stress has an important role in the pathogenesis of hypertension in pregnancy and may be a pathway that can lead to tissue damage. Oxidative stress can stimulate the release of cytokines, antiangiogenic, microparticles and other important molecules in hypertension. Oxidative stress is caused by an imbalance of prooxidants and antioxidants. So we need antioxidants that can suppress oxidative stress in pregnant women with hypertension. Green grass jelly contains alkaloids and flavonoids. Where flavonoids can act as antioxidants and anti-inflammatory. Flavonoids can reduce arterial stiffness making Reactive Oxygen Species (ROS) decrease so that fat peroxide decreases and is followed by decreased oxidative stress, then endothelial function will increase and vasodilation occurs. Malondialdehyde (MDA) is an aldehyde marker compound that is important to see lipid peroxidation and oxidative damage caused by Reactive Oxygen Species (ROS).Objectives: To prove that giving green grass jelly has an effect on reducing oxidative stress in pregnant women.Methods: This study used a quasy experiment with a pretest and posttest control design. A sample of 30 was divided into 2 groups. The group with green grass jelly intervention was 15 people who were given green grass jelly as much as 150 grams per day for 14 days. The second group as many as 15 people as the control group.Results: The green grass jelly intervention group had a significant difference with p-value <0.05. For malondialdehyde results in the control group there was no change in p-value > 0.05. The mean decrease in malondialdehyde levels in the control group was 0.0560 nmol/ml while the average decrease in malondialdehyde in the intervention group was 1.3133 nmol/ml.Conclusions: Green grass jelly is effective and significant for reducing malondialdehyde levels in pregnant women with mild hypertension.